REVISION OF SPIRIFERID BRACHIOPODS OF THE FAMILY UCHTOSPIRIFERIDAE FROM THE DEVONIAN OF SOUTHERN TIMAN - Oleneva N.V. (My University, 2004)
Spiriferid brachiopods of the family Uchtospiriferidae are revised based on the restudy of the original material from the memorial collection of A.I. Ljaschenko. The fact that the changes in the shell micro-ornamentation of Uchtospirifer are controlled both by the ontogenetic development and the degree of preservation is reported for the first time. The variability of the external morphology of spiriferid shells is studied on the basis of biometric analysis. The taxonomic revision results in the recognition of Timanospirifer, Nordispirifer, Clivospirifer, and Acutella as junior synonyms of the genus Uchtospirifer. The description of the type species of the genus, Uchtospirifer nalivkini, is supplemented by new observations.
Keywords: brachiopods; Spiriferida; micro-ornamentation; Devonian; Frasnian; Timan; Russia; Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская::Верхний::Франский